2016
DOI: 10.18632/oncotarget.12982
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of stathmin promotes metastasis and growth of malignant solid tumors: a systemic review and meta-analysis

Abstract: Stathmin has been investigated to be involved in development and progress of malignant tumors. This study was to clarify the relationship between expression of stathmin and tumors and assess its clinical significance. We identified 25 studies with a total of 3,571 individuals from the electronic bibliographic databases and strictly evaluated the quality and heterogeneity of included studies. We analysed the relationship between expression of stathmin and clinical characteristics by the fixed-effects and random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…Each study was judged on eight items, categorized into three groups: the selection of the study groups; the comparability of the groups; and the ascertainment of either the exposure or outcome of interest for case-control or cohort studies respectively. A qualified project was awarded a star and the highest quality research will be awarded 9 stars [9,10]. The two authors performed the evaluation independently.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
“…Each study was judged on eight items, categorized into three groups: the selection of the study groups; the comparability of the groups; and the ascertainment of either the exposure or outcome of interest for case-control or cohort studies respectively. A qualified project was awarded a star and the highest quality research will be awarded 9 stars [9,10]. The two authors performed the evaluation independently.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
“…[19] Recently, over-expression of STMN1 was found to correlate with malignant behavior of tumors, and STMN1 was purported as a molecular biomarker for diagnosis and target for therapy of malignant tumor. [12] In this work, we carried out quantitative phosphoproteomics analysis of STMN1 knockdown CRC cells. Global phosphoproteome analysis has been reported by using stable isotope labeling techniques, e.g.…”
Section: Phosphoproteome Changes Upon Stmn1 Silencing In Cancer Metasmentioning
confidence: 99%
“…[4][5][6][7][8] Recently, it has also been shown to be over-expressed and associated with metastasis, cancer progression, and poor prognosis in several human malignancies. [9][10][11][12][13][14][15][16][17] Similarly, we had reported earlier that STMN1 is a hallmark of CRC progression and predictor for poor survival, [18] and that STMN1 silencing resulted in arrest of tumordisseminative cascades. [19] Our proteome study of STMN1 knockdown cells showed that the protein expression and oncogenic signaling pathways are altered during metastatic transition in CRC, and the proteins that are regulated by STMN1 silencing function predominantly in metastatic processes and signaling.…”
mentioning
confidence: 99%
“…It has been shown to be over-expressed in MM cell lines and tumour samples (45) and it is over expression is consistently associated with increased metastasis and malignant growth (46). Over-expression of miR-223 and siRNA knock-down in MM cell lines reduces stathmin expression, resulting in inhibition of motility and tubulin acetylation via a JNK signalling pathway-dependant mechanism (47).…”
Section: Cancer Genomics and Proteomicsmentioning
confidence: 99%